Opinions of Higher Education Students about Internships and Working while Studying - Kun, András István (International Journal of Engineering and Management Sciences, 2017)
The importance of working while studying in higher education has a globally growing tendency, and Hungary is not an exception. The demand for the opportunities of student employment has been recognized not only by the students but also by the policy makers of higher education, leading to the introduction of solutions like the obligatory internship semesters or the dual training programs. The current study contributes to the better understanding of this field through the analysis of a database from a questionnaire survey conducted among bachelor students from seven majors of the University of Debrecen during the Fall semester in 2015 (N = 589). The main findings suggest that the students mostly consider the internships as an investment into their future career while the short term compensation and the personal interests have a lower importance for them. About 75% of the students would be willing to work not more than 20 hours a week, and most of them would look for ‘official’ studentwork. For working, they would sacrifice the time connected to the following activity-areas (relative to the other activities in the list, and in descending order): time for leisure (this is the most likely to be sacrificed), for sport, for friends, for family, and for learning (this is the less likely to be traded in for working hours). Willingness to work (measured in daily working hours) seems to be connected to the following factors: major, year of study, how important the activity areas are considered compared to working (learning, family, friends, sports, leisure), and the importance of finding a personally interesting internship.